Analysis of Genetic Alterations in Ocular Adnexal Mucosa-Associated Lymphoid Tissue Lymphoma With Whole-Exome Sequencing - Zhao, Andi; Wu, Fangtian; Wang, Yue; Li, Jianyong; Xu, Wei; Liu, Hu (Frontiers in Oncology, 2022)
Next-generation sequencing studies on ocular adnexal marginal zone lymphoma of mucosa-associated lymphoid tissue (OAML) have to date revealed several targets of genetic aberrations. However, most of our current understanding of the pathogenesis and prognosis of OAML is primarily based on studies conducted in populations from Europe and the US. Furthermore, the majority were based on formalin-fixed paraffin-embedded (FFPE) tissue, which generally has poor integrity and creates many sequencing artifacts. To better investigate the coding genome landscapes of OAML, especially in the Chinese population, we performed whole-exome sequencing of 21 OAML cases with fresh frozen tumor tissue and matched peripheral blood samples. IGLL5, as a novel recurrently mutated gene, was found in 24% (5/21) of patients, with a higher relapse rate (P=0.032). In addition, mutations of MSH6, DIS3, FAT1, and TMEM127 were found in 10% of cases. These novel somatic mutations indicate the existence of additional/alternative lymphomagenesis pathways in OAML. Moreover, the difference between our and previous studies suggests genetic heterogeneity of OAML between Asian and Western individuals.